2015
DOI: 10.1371/journal.pone.0140532
|View full text |Cite
|
Sign up to set email alerts
|

Combined Value of Red Blood Cell Distribution Width and Global Registry of Acute Coronary Events Risk Score for Predicting Cardiovascular Events in Patients with Acute Coronary Syndrome Undergoing Percutaneous Coronary Intervention

Abstract: Global Registry of Acute Coronary Events (GRACE) risk score and red blood cell distribution width (RDW) content can both independently predict major adverse cardiac events (MACEs) in patients with acute coronary syndrome (ACS). We investigated the combined predictive value of RDW and GRACE risk score for cardiovascular events in patients with ACS undergoing percutaneous coronary intervention (PCI) for the first time. We enrolled 480 ACS patients. During a median follow-up time of 37.2 months, 70 (14.58%) patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 33 publications
3
18
0
Order By: Relevance
“…combined the predictive value of RDW and GRACE risk score to yield a more accurate predictive value for long-term cardiovascular events in acute coronary syndrome patients who underwent percutaneous coronary intervention as compared to each measure alone. [36] Recently, Yin et al . reported that a combination of RDW and the ASA score may provide a more powerful and effective strategy (AUC increased from 0.700 to 0.723) for the prediction of all-cause mortality in hip fracture patients.…”
Section: Discussionmentioning
confidence: 99%
“…combined the predictive value of RDW and GRACE risk score to yield a more accurate predictive value for long-term cardiovascular events in acute coronary syndrome patients who underwent percutaneous coronary intervention as compared to each measure alone. [36] Recently, Yin et al . reported that a combination of RDW and the ASA score may provide a more powerful and effective strategy (AUC increased from 0.700 to 0.723) for the prediction of all-cause mortality in hip fracture patients.…”
Section: Discussionmentioning
confidence: 99%
“…Global Registry of Acute Coronary Events (GRACE) score was designed to predict the 6-month follow-up morbidity and mortality in patients with acute coronary syndrome [ 13 ]. Later, the ability of GRACE score in risk stratification was demonstrated to have a good predictive value up to 5 years’ follow-up [ 14 ]. Detection of a higher GRACE score was correlated with a poorer prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Venous blood samples were collected from all participants in fasting state, and genomic DNA was extracted from the peripheral blood leukocytes using phenol and chloroform extraction method in Central Laboratory of People's Hospital of Shaanxi Province from January in 2015 to December in 2016 and stored in -80°C refrigerator for further genotyping [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%